The Effect of Alendronate in Male Osteoporosis - Özlem El; Çiğdem Bircan; Ebru Şahin; Burcu Adalmaz; Elif Keskin Pehlivan; Ramazan Kızıl; Özlem Şenocak; Özlen Peker; Sema Öncel (Galenos Yayinevi, 2004)
Osteoporosis in men is increasingly recognized as an important public health issue because of mortality and disability. Approximately 25-30% of all hip fractures occur in men and men are over 3 times more likely to die following a hip fracture than women. Nowadays, the importance of treatment in male osteoporosis is increasing. The aim of this study was to evaluate the effect of alendronate treatment on idiopathic male osteoporosis. Thirty-one male patients with idiopathic osteoporosis were enrolled in the study. The mean age was 63,32±10,26 . All patients were treated with Alendronate 10 mgr/daily and calcium 500 mgr/daily. Bone mineral density (BMD) was measured at baseline and at 1 and 2 years by using Dual Energy X Ray Absorbtiometry at the lumbar spine(L1-4 ) and proximal femur. There was a significant increase from baseline at lumbar spine and femoral BMD after 1 year and 2 years (p< 0,01). Lumbar spine BMD increased by 6% and 11% after 1 and 2 years respectively. Total femur BMD increased by 2.9% after 1 year and 5.1% after 2 years. No significant side effects occured during the study. In summary, alendronate increased lumbar spine and femoral bone mineral density, and was found to be an effective and well-tolerated drug in men with idiopathic osteoporosis.